Accessibility of Slovak towns - Jan Paulov; Ladislav Tolmaci (European Regional Science Association (ERSA), 1998)
Two simple topological and one metric measures were used to characterize the accessibility of 136 Slovak towns. The network of Slovakia with green-line buss stops was conceptualized as a graph. The first measure is defined as number of edges ending in the vertice, the second as a number of edges between selected vertice and all other vertices of the graph using the shortest path. The third measure represents the metric version of the second. According to the first measure Bratislava, the capital of Slovakia, takes the first position. It is followed by Ko?ice, the second largest town of Slovakia. According to the second measure the town of Nitra located in the south-west of Slovakia, takes the first position. According to the third measure the town of ?iar nad Hronom located in central Slovakia, takes the first position. The authors try also to consider possible associations between accessibility and regional development.
Keywords: 330